(untitled) - Cecil B. Currey (Hà Nội, 2014)
Nội dung sách giới thiệu về thời kỳ lịch sử: An xá 1911-1940; Hà Nội 1941-1946; Điện Biên Phủ 1946-1954; Sài Gòn 1955-1991.
Keywords: General,Đại tướng; Biography,Tiểu sử; Vietnam,Việt Nam